Path Analysis on Factors Affecting the Choice of Female Surgical Contraceptive Method in Kendal, Central Java - Maghfiroh, Ainul; Budihastuti, Uki Retno; Nurhaeni, Ismi Dwi Astuti (Journal of Maternal and Child Health, 2019)
Background: Indonesia is one of the developing countries with a high rate of population growth. The government established a Family Planning program in overcoming this problem with effective use of the female surgery contraception. This study aimed to analyze the determinants of female surgery contraceptive method using path analysis model.Subject and method: A retrospective case-control study was conducted in Kendal, Central Java. A sample of 200 women was selected for this study by fixed diseases sampling. The dependent variable was the choice of female surgery contraceptive method. The independent variables were age, education, number of children alive, employment, knowledge, attitude, self-efficacy, husband support, and perception of gender equality. The data were collected by questionnaire and analyzed by path analysis.Results: The choice of female surgery contraception method was directly and positively associated with good knowledge (b= 1.91; 95% CI= 0.80 to 3.02; p= 0.001), positive attitude (b= 1.56; 95% CI= 0.45 to 2.66; p= 0.006), good gender equality perception (b= 1.25; 95% CI= 0.18 to 2.32; p= 0.021), high self efficacy (b= 1.61; 95% CI= 0.48 to 2.74; p= 0.005), high education (b= 1.18; 95% CI= 0.02 to 2.35; p= 0.045), strong husband support (b= 1.24; 95% CI= 0.14 to 2.39; p= 0.027), working outside the home (b= 1.14; 95% CI= 0.06 to 2.21; p= 0.037 ), number of children alive ≥3 (b= 1.74; 95% CI= 0.61 to 2.88; p= 0.003), and maternal age ≥35 years (b= 1.57; 95% CI = 0.34 to 2.75; p= 0.012). It was indirectly associated with age and education.Conclusions: The choice of female surgery contraception method is directly and positively associated with good knowledge, positive attitude, good gender equality perception, high self-efficacy, high education, strong husband support, working outside the home, number of children alive ≥3, and maternal age ≥35 years. It is indirectly associated with age and education.Keywords: female surgery contraceptive method, determinant, path analysisCorrespondence: Ainul Maghfiroh. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Email: Ainulmaghfiroh0504@gmail.com. Mobile: +6285641012090.Journal of Maternal and Child Health (2019), 4(3): 146-157https://doi.org/10.26911/thejmch.2019.04.03.02